Trace element and OH content of quartz grains in the Amazon river: Potential application in provenance analysis - R. Stalder; D. Jaeger; S. Andò; E. Garzanti; C.M. Chiessi; A.O. Sawakuchi; T. Ludwig; M. Strasser (Sedimentary Geology, 2025)

Japan Trench event stratigraphy: First results from IODP giant piston coring in a deep-sea trench to advance subduction zone paleoseismology - Michael Strasser; Ken Ikehara; Charlotte Pizer; Takuya Itaki; Yasufumi Satoguchi; Arata Kioka; Cecilia McHugh; Jean-Noel Proust; Derek Sawyer; J. Everest; L. Maeda; K. Hochmuth; et al. (Marine Geology, 2024)

The increasing threat to European forests from the invasive foliar pine pathogen, Lecanosticta acicola - K. Tubby; K. Adamčikova; K. Adamson; M. Akiba; I. Barnes; P. Boroń; H. Bragança; T. Bulgakov; N. Burgdorf; P. Capretti; T. Cech; M. Cleary; et al. (Forest Ecology and Management, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Ground speed and planter downforce influence on corn seed spacing and depth - S. A. Badua; A. Sharda; R. Strasser; I. Ciampitti (Precision Agriculture, 2021)

A tsunamigenic delta collapse and its associated tsunami deposits in and around Lake Sils, Switzerland - Valentin Nigg; Stephan Wohlwend; Michael Hilbe; Benjamin Bellwald; Stefano C. Fabbri; Gregory F. de Souza; Florian Donau; Reto Grischott; Michael Strasser; Flavio S. Anselmetti (Natural Hazards, 2021)
Large lacustrine mass movements and delta collapses are increasingly being considered as potential tsunamigenic sources and therefore hazardous for the population and infrastructure along lakeshores. Although historical reports document tsunami events in several lakes in Switzerland, and although the propagation of lake tsunamis has been studied by numerical wave modeling, only little is known about on- and offshore lacustrine tsunami deposits. In Lake Sils, Switzerland, a large prehistoric mass-movement deposit originating from the Isola Delta with a minimum estimated volume of 6.5 × 10 6 m 3 and a basinal thickness of > 6 m in the seismic record has been identified by previous studies and radiocarbon dated to around 700 Common Era. Here, we combine (i) comprehensive sedimentological investigation of sediment cores recovered from the on- and offshore settings, (ii) mineralogical fingerprinting of the inflows from key catchments to characterize sediment provenance, and (iii) numerical tsunami modeling, to test the hypothesis of a tsunamigenic delta collapse in Lake Sils. We observe a clastic event deposit consisting of coarse-grained, fining-upward sand overlying an organic-rich peat deposit in the shallow water. This layer thins and fines landward on the coastal plain. Toward the deeper water (20–40 m), the deposit transforms into a thicker and more heterogeneous sediment package with multiple sequences of fining-upward sand and a well-pronounced clay cap at the top. Radiocarbon dating of the peat underlying the event deposit yields a maximum age of 225–419 calibrated Common Era. The tsunami models, which indicate wave heights reaching up to 5 m, simulate areas of inundation that coincide with the location of event deposits. Based on our results, we propose that the historically undocumented Isola Delta collapse generated a basin-wide tsunami that inundated the lakeshore, transporting large amounts of unconsolidated sediment along the lakeshore toward the coastal plain and into the deeper lake basin.

Overloaded! Critical revision and a new conceptual approach for snow indicators in ski tourism - B. Abegg; S. Morin; O. C. Demiroglu; H. François; M. Rothleitner; U. Strasser (International Journal of Biometeorology, 2021)
Indicators are widely used in climate variability and climate change assessments to simplify the tracking of complex processes and phenomena in the state of the environment. Apart from the climatic criteria, the snow indicators in ski tourism have been increasingly extended with elements that relate to the technical, operational, and commercial aspects of ski tourism. These non-natural influencing factors have gained in importance in comparison with the natural environmental conditions but are more difficult to comprehend in time and space, resulting in limited explanatory power of the related indicators when applied for larger/longer scale assessments. We review the existing indicator approaches to derive quantitative measures for the snow conditions in ski areas, to formulate the criteria that the indicators should fulfill, and to provide a list of indicators with their technical specifications which can be used in snow condition assessments for ski tourism. For the use of these indicators, a three-step procedure consisting of definition, application, and interpretation is suggested. We also provide recommendations for the design of indicator-based assessments of climate change effects on ski tourism. Thereby, we highlight the importance of extensive stakeholder involvement to allow for real-world relevance of the achieved results.

Somatic NRAS mutation in patient with generalized lymphatic anomaly - Eugenia Manevitz-Mendelson; Gil S. Leichner; Ortal Barel; Inbal Davidi-Avrahami; Limor Ziv-Strasser; Eran Eyal; Itai Pessach; Uri Rimon; Aviv Barzilai; Abraham Hirshberg; Keren Chechekes; Ninette Amariglio; et al. (Angiogenesis, 2018)

A subaqueous hazard map for earthquake-triggered landslides in Lake Zurich, Switzerland - M. Strupler; L. Danciu; M. Hilbe; K. Kremer; F. S. Anselmetti; M. Strasser; S. Wiemer (Natural Hazards, 2018)

Internal deformation of a muddy gravity flow and its interaction with the seafloor (site C0018 of IODP Expedition 333, Nankai Trough, SE Japan) - J. S. Laberg; M. Strasser; T. M. Alves; S. Gao; K. Kawamura; A. Kopf; G. F. Moore (Landslides, 2017)

Probabilistic stability evaluation and seismic triggering scenarios of submerged slopes in Lake Zurich (Switzerland) - M. Strupler; M. Hilbe; F. S. Anselmetti; A. J. Kopf; T. Fleischmann; M. Strasser (Geo-Marine Letters, 2017)

Modeling the Effect of the Selective S1P1 Receptor Modulator Ponesimod on Subsets of Blood Lymphocytes - Dominik Lott; Andreas Krause; Christian A. Seemayer; Daniel S. Strasser; Jasper Dingemanse; Thorsten Lehr (Pharmaceutical Research, 2017)

Twentieth century seismicity of the Koffiefontein region (Free State, South Africa): consistent determination of earthquake catalogue parameters from mixed data types - F. O. Strasser; P. Albini; N. S. Flint; C. Beauval (Journal of Seismology, 2015)

Earthquakes from 1820 to 1936 in Grahamstown and surroundings (Eastern Cape Province, South Africa) - Paola Albini; Fleur O. Strasser; Nicolette S. Flint (Bulletin of Earthquake Engineering, 2014)

An intensity database for earthquakes in South Africa from 1912 to 2011 - V. Midzi; J. J. Bommer; F. O. Strasser; P. Albini; B. S. Zulu; K. Prasad; N. S. Flint (Journal of Seismology, 2013)

A hypothesis of the Senoumi submarine megaslide in Suruga Bay in Japan—based on the undrained dynamic-loading ring shear tests and computer simulation - K. Sassa; B. He; T. Miyagi; M. Strasser; K. Konagai; M. Ostric; H. Setiawan; K. Takara; O. Nagai; Y. Yamashiki; S. Tutumi (Landslides, 2012)

Exogenous glycine betaine and proline play a protective role in heat-stressed barley leaves ( Hordeum vulgare L.): A chlorophyll a fluorescence study - A. Oukarroum; S. El Madidi; R. J. Strasser (Plant Biosystems, 2012)

Mapping basin-wide subaquatic slope failure susceptibility as a tool to assess regional seismic and tsunami hazards - Michael Strasser; Michael Hilbe; Flavio S. Anselmetti (Marine Geophysical Research, 2011)

Receptor-independent sensitization of the adenylyl cylase after chronic treatment with cyclosporine A - G. Simonis; T. Christ; S. K. Bährle; M. Pena; S. P. Schoen; R. Marquetant; U. Ravens; R. H. Strasser (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

JIP test for fast fluorescence transients as a rapid and sensitive technique in assessing the effectiveness of arbuscular mycorrhizal fungi in Zea mays : Analysis of chlorophyll a fluorescence - M. K. Rai; S. Shende; R. J. Strasser (Plant Biosystems, 2008)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

Analysis of mechanisms contributing to AraC-mediated chemoresistance and re-establishment of drug sensitivity by the novel heterodinucleoside phosphate 5-FdUrd-araC - S. Maier; S. Strasser; P. Saiko; C. Leisser; S. Sasgary; M. Grusch; S. Madlener; Y. Bader; J. Hartmann; H. Schott; R. M. Mader; T. Szekeres; et al. (Apoptosis, 2006)

The influence of redox conditions in soils on extraplasmatic Fe-loading of plant roots - S. Fiedler; O. Strasser; G. Neumann; V. Römheld (Plant and Soil, 2004)